A method for calculating permanent displacement of seismic-induced bedding rock landslide considering the deterioration of the structural plane - Peng, Yulin; Dong, Shan; Lu, Zhichun; Zhang, Heng; Hou, Weihua (Frontiers in Earth Science, 2023)
The mechanism of seismic-induced bedding rock landslide is distinct from that of slope instability/landslide in normal gravity conditions; their failure modes are mainly characterized by vibration deterioration effect of rock mass structural plane due to a seismic loading, which has a significant effect on the stability of the bedding rock landslide. Several advanced methods have been proposed to assess earthquake-induced bedding rock landslide. However, the quantitative evaluation of the vibration deterioration effect of structural plane, along with its application in the dynamic stability analysis of bedding rock slopes, remains a challenging topic that requires further study. In this study, on the basic of the analysis of the cyclic shear condition and the cyclic shear test of the structural plane, the expressions to calculate the dilatancy angle and basic friction angle of structural plane under cyclic shear loading are studied. A deterioration formula for structural plane shear strength is proposed, which fully considers the deterioration effect during cyclic shear. Furthermore, a new calculating method of the seismic-induced permanent displacement of the bedding rock landslide, which introduces the deterioration effect of the structural plane, is developed. A case study was used to compare the permanent displacement calculated with the proposed method with those obtained using the Newmark and Qi methods, which demonstrates the effectiveness and applicability of the proposed method.